The Risk-sensitivity of Bank Capital Requirements: The Moderating Effects of Capital Regulation and Supervisory Power - Albaity, Mohamed; Toobaee, Mohammadmahdi (International Journal of Economics and Financial Issues, 2017)
This study examines the moderating effects of capital regulation and supervisory power on the risk-sensitivity of bank capital requirements. Using two-step system GMM estimator, we work on the international sample of 222 banks charted in 30 countries. The finding suggests that asset volatility is a critical variable in explaining the risk-sensitivity of banks. The results indicate that stricter capital regulatory regimes and higher supervisory power enhance the risk sensitivity of capital requirements. Moreover, the capital regulation was found to moderate the relationship between asset volatility and risk-sensitivity while supervisory power was found not to exert any impact on the level of risk of the banks. Another interesting result is that governments with a higher debt to GDP ratio tend to overregulate the other banks' investments compared to government bonds. This is the first study that investigates the moderating effects of capital regulation and power of supervision on the risk sensitivity of capital requirements. The results of this study show that the efficiency of risk-based capital requirements depends on the stringency of capital regulation in different countries. Keywords: bank capital requirements, risk-weighted assets, capital regulation, supervisory power, system GMM, government debt to GDP. JEL Classifications: G21, G34, G33, G28